2004
DOI: 10.1007/s10072-003-0194-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha serum levels and inflammatory response in acute ischemic stroke patients

Abstract: Experimental evidence indicates that tumor necrosis factor alpha (TNF-alpha) is involved in brain damage following ischemic injury. The present study was designed to monitor serum TNF-alpha levels in acute stroke patients and to correlate TNF-alpha levels with lesion size, neurological impairment and vascular risk factors. In 41 patients with ischemic stroke, serum TNF-alpha levels were serially measured by a solid enzyme amplified sensitivity immunoassay (EASIA) in the first 10 days after stroke onset. Serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 38 publications
2
50
1
2
Order By: Relevance
“…33 TNF-a release from blood cells and serum levels of TNF-a were found to be elevated during the acute phase following stroke compared with healthy controls. [34][35][36] Furthermore, increased levels of TNF-a in the cerebral spinal fluid and serum of acute stroke patients has been associated with increased severity of postischemic neuropathology 37 and polymorphism of the TNF gene have been associated with susceptibility to ischemic stroke. 32 IL-6 is a pleiotropic cytokine involved in inflammatory processes and like IL-1 is able to induce acute inflammatory responses such as fibrinogen and C-reactive protein production.…”
Section: Resultsmentioning
confidence: 99%
“…33 TNF-a release from blood cells and serum levels of TNF-a were found to be elevated during the acute phase following stroke compared with healthy controls. [34][35][36] Furthermore, increased levels of TNF-a in the cerebral spinal fluid and serum of acute stroke patients has been associated with increased severity of postischemic neuropathology 37 and polymorphism of the TNF gene have been associated with susceptibility to ischemic stroke. 32 IL-6 is a pleiotropic cytokine involved in inflammatory processes and like IL-1 is able to induce acute inflammatory responses such as fibrinogen and C-reactive protein production.…”
Section: Resultsmentioning
confidence: 99%
“…On the other, they can facilitate thrombogenesis by increasing the levels of plasminogenactivating inhibitor-1 tissue factor (PAI-1), and platelet activating factor and by inhibiting tissue plasminogen activator and protein [121]. Clinical studies [122,123] have reported increased levels of proinflammatory cytokines and adhesion molecules in the peripheral blood and cerebrospinal fluid (CSF) of patients with ischemic stroke. Among the cytokines involved in the pathogenesis of ischemic stroke, TNF-is activated in experimental ischemia at both the mRNA and protein levels.…”
Section: Inflammation In Acute Stroke Subtypesmentioning
confidence: 99%
“…Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. (Intiso et al, 2004). On the other hand, TNF-α is also produced in brain, by microglia and astrocytes, both of which are activated by LPS.…”
mentioning
confidence: 99%
“…during stroke (Intiso et al, 2004). On the other hand, TNF-α is also produced in brain, by microglia and astrocytes, both of which are activated by LPS.…”
mentioning
confidence: 99%